2020
DOI: 10.1002/asi.24409
|View full text |Cite
|
Sign up to set email alerts
|

One size does not fit all: A study of badge behavior in stack overflow

Abstract: Badges are endemic to online interaction sites, from question and answer (Q&A) websites to ride sharing, as systems for rewarding participants for their contributions. This article studies how badge design affects people's contributions and behavior over time. Past work has shown that badges “steer” people's behavior toward substantially increasing the amount of contributions before obtaining the badge, and immediately decreasing their contributions thereafter, returning to their baseline contribution levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 26 publications
2
18
0
3
Order By: Relevance
“…Our results revealed the following insights: First, more than 60% of the users are not steered, in that they exhibit a consistent activity rate in SO that is not effected by the badge. We prove that a "bump" in activity that is conveyed by prior work arises as an artifact of centering the data on the day of badge achievement [1,28]. We call this phenomenon the Phantom Steering Effect.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…Our results revealed the following insights: First, more than 60% of the users are not steered, in that they exhibit a consistent activity rate in SO that is not effected by the badge. We prove that a "bump" in activity that is conveyed by prior work arises as an artifact of centering the data on the day of badge achievement [1,28]. We call this phenomenon the Phantom Steering Effect.…”
Section: Introductionmentioning
confidence: 65%
“…Other studies have independently confirmed that the presence of online badges increases the probability that a user will act in a manner to achieve the badge, as well as the rate at which the user will perform those actions [6,14,21,28]. Kusmierczyk and Gomez-Rodriguez [21] highlight the importance of modelling the "utility heterogeneity" among the users but they study badges which have a threshold of 1 action and do not characterise how one might change one's behaviour in the presence of the badge incentive.…”
Section: The Study Of Online Badgesmentioning
confidence: 92%
See 2 more Smart Citations
“…Once a user receives a badge by achieving a certain goal, a more challenging badge appears as his/her next goal to achieve. Badges also track users' performance such as points, allowing them to compare their performance with others (Rigby and Ryan, 2011; Yanovsky et al , 2020). Thus, users can use badges to set goals, take up challenges and make social comparisons.…”
Section: Theoretical Backgroundmentioning
confidence: 99%